2001
DOI: 10.1136/adc.85.6.463
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilisation of infants with chronic lung disease, related to hospitalisation for RSV infection

Abstract: Aims-To compare the use of health care resources and associated costs between infants with chronic lung disease (CLD) who had or had not an admission with a proven respiratory syncytial virus (RSV) infection. Methods-Review of community care, outpatient attendances, and readmissions in the first two years after birth. Patients: 235 infants (median gestational age 27 weeks) evaluated in four groups: 45 infants with a proven RSV admission (RSV proven); 24 with a probable bronchiolitis admission; 60 with other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 16 publications
5
152
0
Order By: Relevance
“…Preterm infants with BPD have an increased frequency of health care utilisation and hospital admissions due to acute respiratory infections compared to those without BPD [2,38,46]. Approximately, 50 to 73% of preterm infants with BPD were re-hospitalised at least once with an acute respiratory infection during the first 3 years of life, which is nearly twice the frequency of re-hospitalisation among those without BPD [7,47,48]. The risk of re-hospitalisation due to acute respiratory infection is significantly higher among infants with BPD who remain oxygen dependent after discharge during the first 3 years of life, compared to those who are not oxygen dependent at discharge (70% vs. 58% respectively; P  < 0.001) [48].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Preterm infants with BPD have an increased frequency of health care utilisation and hospital admissions due to acute respiratory infections compared to those without BPD [2,38,46]. Approximately, 50 to 73% of preterm infants with BPD were re-hospitalised at least once with an acute respiratory infection during the first 3 years of life, which is nearly twice the frequency of re-hospitalisation among those without BPD [7,47,48]. The risk of re-hospitalisation due to acute respiratory infection is significantly higher among infants with BPD who remain oxygen dependent after discharge during the first 3 years of life, compared to those who are not oxygen dependent at discharge (70% vs. 58% respectively; P  < 0.001) [48].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Four out of 10 (40%) of ICU admissions in our study were related to RSV infection. Greenough, et al in their retrospective review concluded that RSV hospitalization in patients with chronic lung disease is associated with increased ICU admission, and longer duration of ICU stay [6].…”
Section: Icu Admissionsmentioning
confidence: 99%
“…Re-hospitalization after initial discharge from NICU for preterm infants has been examined in various settings across the world [1][2][3][4][5][6][7][8][9][10][11][12][13]. Reasons for re-hospitalizations in extreme preterm infants can be related either to medical (bronchiolitis, lower-respiratory tract infection, asthma, reflux disease) or to surgical (PEG related problems, V-P shunt related issues, hernia repair) causes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Up to 14% of all premature infants will be hospitalized with bronchiolitis early in life, and they will typically have a more severe course and a longer length of stay (LOS) than full term infants. [5][6][7] More than one-half of premature infants <29 weeks' gestational age may be admitted during infancy for respiratory distress, 8 and up to 1 in 4 patients <28 weeks' gestational age will exhibit moderate to severe respiratory dysfunction even at 2 years of age. 9 Furthermore, diminished lung function in premature infants has been associated with increased likelihood of severe illness.…”
Section: The Clinical Management Of Preterm Infants With Bronchiolitismentioning
confidence: 99%